A heritage of colour natural dyes past and present - Dean, Jenny (Tunbridge Wells, Kent Search Press, 2014)
"A heritage of color explores the techniques that can be used to create a wealth of colors from over 50 plants, including many that have been in constant use as dyes for more than 2000 years. Inspired by the colors on textile fragments from the iron age and by the achievements of early dyers the author describes some of the dyes and methods of the past and considers how they can be adapted for use today. The book covers all the basics of natural dyeing and explains in detail how to experiment with local plants, wherever you may live, to produce a wide range of beautiful, rich colors on textile fibres. A heritage of color also includes information on growing many of the dye plants and sections on dyeing fungi, contact printing on cloth and dyeing multi-colored fibres and fabrics. The emphasis throughout is on environmentally-friendly methods and on the thrill of personal discovery through practical experience." -- Provided by publisher
Introduction -- Inspiration from the past -- Environmental considerations -- The basics -- Other techniques -- The dye plants -- Using lichens for dyeing -- Using fungi for dyeing -- A brief outline of some of the dyes used in Europe from the iron age to the middle ages -- Health and safety information.
Includes bibliographical references (page 154-155) and index.
Keywords: Dyes and dyeing, Domestic; Dye plants